University curriculum and employability needs. - Shuib, Munir (National Higher Education Research Institute, Universiti Sains Malaysia, 2010)
University curriculum that meets employability needs is deemed as an important factor in enhancing human capital development. Unemployment among public higher education institution graduates has dominated much public discussion in Malaysia and the university curricula in preparing students for the workplace has been questioned. This book reports the findings of a study that has aimed to examine the skills and competencies as required by employers in the workplace in the fields of Science, Information and Communications Technology so that current development trends can inform the designing of the university curriculum. The discussion engages quantitative and qualitative methods to elicit views from the industry managers, academics and graduates on four areas: digital age literacy skills, effective communication skills, inventive thinking skills and high productivity skills.